The Invention of Enterprise : Entrepreneurship from Ancient Mesopotamia to Modern Times - Baumol, William J.; Mokyr, Joel; Landes, David S. (Book collections on Project MUSE., 2010)
This work provides a sweeping history of enterprise in Mesopotamia and Neo-Babylon; carries the reader through the Islamic Middle East; offers insights into the entrepreneurial history of China, Japan, and colonial India; and describes the crucial role of the entrepreneur in innovation activity in the Western world.